Randang in Nagari Salimpauang, Kabupaten Tanah Datar - Hidayatul Rahmi; Lucy Fridayati (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
This research was motivated by the researchers' curiosity to obtain accurate knowledge about randang in Nagari Salimpauang, Tanah Datar Regency. In addition, the unique randang there is the talua randang, where the taluas are steamed first. The purpose of this study was to identify the ingredients, spices, tools, and processing techniques for randang in Nagari Salimpauang. This type of research is qualitative research with descriptive methods. Data sources were obtained from Bundo Kanduang and women who were experts in making randang. This research data collection technique through observation, interviews, and documentation. Field data analysis which includes data reduction, data presentation, conclusions, and data verification. The results of the study concluded that the ingredients and spices used included beef, chicken, taro, thick coconut milk, shallots, garlic, galangal, ginger, turmeric, red chilies, wheat flour, coriander, lime leaves, bay leaves, and turmeric leaves. The tools used are knife, basin, cutting board, blende, plate, millstone, skillet, sanduak, gas stove, stove, samba plate, and cambuang. Randang processing technique is done traditionally with a furnace and modernly with a gas stove.